2018
DOI: 10.1016/j.omtm.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of Precision-Cut Lung Slices as an Ex Vivo Tool for Evaluating Viruses and Viral Vectors for Gene and Oncolytic Therapy

Abstract: Organotypic slice cultures recapitulate many features of an intact organ, including cellular architecture, microenvironment, and polarity, making them an ideal tool for the ex vivo study of viruses and viral vectors. Here, we describe a procedure for generating precision-cut ovine and murine tissue slices from agarose-perfused normal and murine melanoma tumor-bearing lungs. Furthermore, we demonstrate that these precision-cut lung slices can be maintained up to 1 month and can be used for a range of applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…Ovine lung slices were transduced with GFP-expressing LVs since we previously found that lung tissue from lambs <6 months of age expresses a heatresistant AP. 26 Forty-eight hours post-transduction, the lung tissue slices were sandwiched between a coverslip and glass slide and imaged with an inverted fluorescence microscope. Faint GFP-positive foci observed in ovine lung tissue slices transduced by EBOV GP LV are pinpointed by yellow arrows.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ovine lung slices were transduced with GFP-expressing LVs since we previously found that lung tissue from lambs <6 months of age expresses a heatresistant AP. 26 Forty-eight hours post-transduction, the lung tissue slices were sandwiched between a coverslip and glass slide and imaged with an inverted fluorescence microscope. Faint GFP-positive foci observed in ovine lung tissue slices transduced by EBOV GP LV are pinpointed by yellow arrows.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we generated two novel LVs pseudotyped with DGP Jenv N592T and DGP Jenv M593E, mutant versions of the envelope glycoprotein from a lung tropic betaretrovirus, which can produce vector titers equivalent to VSVg LV, and optimized a method for their large-scale purification. Using a lung slice method we previously optimized, 26 we developed a novel murine lung tissue slice model that allowed us to test these pseudotyped LVs ex vivo. We showed that TFF, followed by gradient ultracentrifugation, dialysis, and PEG-20,000 concentration, is a scalable method for producing high-titer DGP Jenv-pseudotyped LVs for in vivo use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these technologies, organotypic slice cultures have demonstrated the ability to closely resemble the TME architecture and allow for drug metabolism and toxicity studies in brain, 33 liver, [34][35][36] lung, 36,37 kidney, 36,38 and intestine 34 tumor slices. Patient-derived clinical samples provide a unique tool to explore the susceptibility of individual tumors to specific therapies, but the small amount of tumor tissue extracted from any given patient limits the utility of this approach.…”
Section: Introductionmentioning
confidence: 99%